Primary Hepatoid Adenocarcinoma of Gallbladder With MB21D2/GALNT12/ARID2 Mutations: A Case Report - Li, Zhenyu; Jiang, Qingming; Chen, Xinyu; Xiao, Yu; Xiao, Jue (Frontiers in Endocrinology, 2022)
Background: Primary hepatoid adenocarcinoma of gallbladder is a relatively rare of extrahepatic adenocarcinoma. The genetic changes involved this type of adenocarcinoma was unexplained so far. We reported a rare case of primary hepatoid adenocarcinoma of gallbladder with Mab-21 domain containing 2 (MB21D2), polypeptide N-acetylgalactosaminyltransferase 12 (GALNT12), and AT-rich interaction domain 2 (ARID2) mutations which was confirmed after surgical resection pathologically. Case summary: A 69-years-old female with distention of hypogastrium and constipation, received enema treatment, but ineffectively. No abnormalities was found on relevant physical examination. And then, the CT and MRI demonstrated a 3.3-4 cm soft tissue mass shadow in the neck of gallbladder. The primary lesions consisted of two components, high-grade intraepithelial neoplasia of glands and hepatoid glands microscopically after laparoscope cholecystectomy. Immunohistochemical staining shown the sameness and difference of the two areas. Furthermore, Tumor mutational burden (TMB) shown MB21D2, GALNT12, and ARID2 gene was mutated. Conclusion: This is the first report of primary hepatoid adenocarcinoma of gallbladder with MB21D2, GALNT12 and ARID2 mutations. This will provide a theoretical basis for genetic changes in rare tumors.